2012
DOI: 10.1002/qj.1925
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown of hydrostatic balance at convective scales in the forecast errors in the Met Office Unified Model

Abstract: For data assimilation in numerical weather prediction, the initial forecast-error covariance matrix P f is required. For variational assimilation it is particularly important to prescribe an accurate initial matrix P f , since P f is either static (in the 3D-Var case) or constant at the beginning of each assimilation window (in the 4D-Var case). At large scales the atmospheric flow is well approximated by hydrostatic balance and this balance is strongly enforced in the initial matrix P f used in operational va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…The B matrix is normally modelled with guidance from large-scale dynamics, namely that geostrophic balance is dominant, and hydrostatic balance is exact. These assumptions are probably not applicable at convective scales (as shown by Berre, 2000, Bannister et al, 2011, Vetra-Carvalho et al, 2012, Bannister, 2015, and as we have seen here, where more imbalance is present at the smaller scales). A key idea which will be explored in a forthcoming paper is to use the normal mode structure of the linearised equations to define the B matrix rather than relying on imposed balances.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The B matrix is normally modelled with guidance from large-scale dynamics, namely that geostrophic balance is dominant, and hydrostatic balance is exact. These assumptions are probably not applicable at convective scales (as shown by Berre, 2000, Bannister et al, 2011, Vetra-Carvalho et al, 2012, Bannister, 2015, and as we have seen here, where more imbalance is present at the smaller scales). A key idea which will be explored in a forthcoming paper is to use the normal mode structure of the linearised equations to define the B matrix rather than relying on imposed balances.…”
Section: Discussionmentioning
confidence: 80%
“…In regions of convection, the aspect ratio increases, and thus hydrostatic balance may no longer be a good approximation. Vetra-Carvalho et al (2012) demonstrated that hydrostatic balance breaks down in the UM when it is run at 1.5 km horizontal resolution in regions of convection. At midlatitudes and high latitudes, the geostrophic assumption is accurate for large-scale flows where the Rossby number is small (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This happens at about 25 grid lengths (35 km) inside this convecting region. Vetra-Carvalho et al (2010) compared the vertical correlations of potential temperature perturbations, θ -θ , with those of the 'hydrostatic potential temperature (found from pressure perturbations through (2)), θ H -θ H after degrading the resolution of the fields in a similar way as is done here. For their case study they found that the θ -θ and θ H -θ H correlation matrices differ at horizontal lengthscales below 20 km in convecting regions.…”
Section: Discussionmentioning
confidence: 99%
“…The hydrostatic balance of the initial ensemble perturbations is necessary because the imbalanced initial ensemble perturbations grow during the model integration and degrade the quality of the ensemble forecasts. To measure how this balance is maintained with the initial ensemble perturbations, hydrostatically balanced potential temperature perturbations were calculated using the initial ensemble perturbations from the KMA EPS and UM analyses (see Vetra-Carvalho et al 2012):…”
Section: The Hydrostatic Balance Of the Initial Ensemble Perturbatmentioning
confidence: 99%